Penerapan Model Pembelajaran Kooperatif Tipe Numbereded Heads Together (NHT) Pada Konsep Sistem Pencernaan Makanan Pada Manusia Di Kelas IV SD Negeri Mandalasari 1 Kecamatan Puspahiang Kabupaten Tasikmalaya. - Nuryadin, Egi (Bioedusiana: Jurnal Pendidikan Biologi, 2016)
Research aims to understand match / the accuracy of learning model cooperative type Numbered heads & together ( nht in learning the concept of digestive system food on human beings in fourth grade land mandalasari 1 kecamatan puspahiang the market. A population that used all participants fourth grade students land mandalasari 1 and the Numbered of students 36 people.The whole population of are only sampled the school tuition fourth grade land mandalasari 1 in 36 people.An instrument used in this research was the test results student learning the concept digestive system food in humans.This test of tests the form of an option double with 4 option. Analysis techniques the data used was the median t and tests. The results showed based on analysis of the median test scores me is greater than values me determined. So the application of learning model cooperative type Numbered heads together ( nht ) match is applied to explain the digestive system food on human beings in fourth grade mandalasari 1 .Keywords: Cooverative learning model, Numbereded heads together, cognitive learning result